Contradiction of Ideas in George Bernard Shaw’s Mrs Warren’s Profession - Setiawan, Rendriyanto (Journal of English Department WM, 2013)
Mrs Warren’s Profession categorized as play unpleasant by its author George Bernard Shaw, is one of world most famous and controversial plays. The play, unlike other play during its era, uses the corruption and hypocrisy from the upper class of Victorian Era society as the theme. The play is purposed by the author as a scathing criticism to its theme. This purpose is materialized on the ideas represented by the two major female characters in the play. Uniquely, these ideas differs greatly to one on another until it looks like a there is decent contradiction on it. From this point, this paper aims at finding out ideas represented by the two major female characters. There are two major female characters being analyzed, Vivie Warren, a Cambridge graduate and Mrs Warren, both Vivie Warren’s estranged mother and a brothel owner. The finding of the major female characters ideas takes lengthy but worthful steps. The writer first has to read the script of the play five times. The first and second one are to know the overall of the drama and take notes of interesting things on the play. When the writer does those two steps above he also selects the narrations and dialogs in the play are related to the topics and also reads and analyzes other books and sources related to the topics of the thesis. Those steps above are essential to gather data that will be used to reveal setting, characters, plot and, theme of the play in order to do the analysis. He later read the play three more times to group the topics on the play, categorizes the idea of the major female characters and make sure all ideas are on its correct place.